DIKSI KIKIR DALAM AL-QUR’AN: STUDI KOMPARATIF TAFSIR JAMI’ AL-BAYAN FI TA’WIL AL-QUR’AN DAN TAFSIR AL-TAHRIR WA AL-TANWIR - Lina Roaitul Aini; Moh. Jufriyadi Sholeh (MAHAD ALY JOURNAL OF ISLAMIC STUDIES, 2025)
The Qur'an is a miracle of Allah SWT to all mankind, one of the miracles of the Qur'an can be reviewed from the aspect of language, the concept of taraduf is part of the ulm of the Qur'an which is very interesting to discuss, the words that contain the meaning of taraduf are used in different contexts with the meaning of the words having a more specific essence, the difference in vocabulary used is one of the factors in the differences in the objects discussed in each verse. Stingy is one of the words that contains taraduf, the Qur'an mentions the word stingy with different diction. Stingy is a despicable trait that arises from excessive egoistic behavior, people who have a stingy nature tend to have hard hearts and have no empathy. In this study, the researcher used a qualitative approach with a library research approach. The primary data sources used in this study are Tafsir Jami’ Al-Bayan Fi Ta’wil Al-Qur’an by al-Tabari and Tafsir Al-Tahrir wa Al-Tanwir by Ibn ‘Asyur using descriptive analysis method and comparative method. The results of this study are a. Bukhl is a person who does not want to spend his wealth and invites others to do the same. b. Syuh is used to explain a trait that is stingier than bukhl, Syuh is bukhl accompanied by lust. c. Danin refers to a person who is stingy with the knowledge he has. d. Syadid in QS. Al-Adiyat/100: 8 is a person who holds his wealth tightly. d. Qatur is interpreted as a person who is too frugal.